Effect of Ethanolic Stem Extract of Nelsonia Canescens on Selected Biochemical Parameters in Male Wistar Rats Induced with Sodium Arsenite - David, Bando Christopher; Tutuwa, Jummai Adamu; Tadawus, Rejoice Habila; Ogu, Emmanuel Odiba; Ifraimu, Daniel; Sunday, Oche Gabriel; Jesse, Polly Shingu; Agbu, Tsoken Danji (Journal of Multidisciplinary Science: MIKAILALSYS, 2024)
Medicinal plants are those that have curative qualities or have positive pharmacological effects on the human body. The effect of ethanolic stem extracts from Nelsonia canescens was studied in relation to Sodium arsenite-induced toxicity in wistar rats. Fresh stem extract of Nelsonia canescens were obtained behind rice mill area, Wukari, Taraba state and was shade dried at room temperature and was homogenized into powder and measured at 300g into 100ml of absolute ethanol for 72 hours. 15 healthy male rats of 70g to 90g weight were obtained from animal house Makurdi, Benue state. Animals from Group 1 were used as control. 5mg/kg body weight of Sodium arsenite was administered to Group 2 animals while animals in Groups 3, 4 and 5 were administered with Nelsonia canescens ethanolic stem extracts 50 mg/kg, 100mg/kg and 200 mg/kg as well. At the end of 3 weeks the animals were sacrificed and serum sample were collected and analysed using standard methods. The results indicate that, when compared to those who received Sodium arsenite, those who received ethanol stem extracts of Nelsonia canescens showed a comparatively considerable liver protection against Sodium arsenite -induced damage. The levels of biochemical parameters: Albumin, Total protein, Alanine aminotransferase (ALT), Aspartate aminotransferase (AST), Alkaline phosphatase (ALP), Total bilirubin, Urea, Creatinine of rats administered with Sodium arsenite only was also observed. The Nelsonia canescens extract’s activity at 200mg/kg bw (higher dose) give a reasonable decrease in the amount of these liver enzymes. Deducing from study results, it indicates that Nelsonia canescens leaf extracts could be an effective agent in Sodium arsenite mediated liver toxicity in adult wistar rats and drug development.